The Body Position Spatial Task, a Test of Whole-Body Spatial Cognition: Comparison Between Adults With and Without Parkinson Disease. (November 2018) - Battisto, Jessica; Echt, Katharina V.; Wolf, Steven L.; Weiss, Paul; Hackney, Madeleine E.
Background . The Body Position Spatial Task (BPST) is a novel measure of whole-body spatial cognition involving multidirectional steps and turns. Individuals with Parkinson disease (PD) are affected by motor and cognitive impairments, particularly in spatial function, which is important for mental imagery and navigation. Performance on the BPST may inform understanding of motor-cognitive and spatial cognitive function of individuals with PD. Objectives . We conducted this study to determine feasibility and validity of the BPST with standard, validated, and reliable measures of spatial cognition and motor-cognitive integration and to compare BPST performance in adults with and without PD. Methods . A total of 91 individuals with mild-moderate PD and 112 neurotypical (NT) adults of similar age were recruited for the study to complete the BPST and other measures of mobility and cognition. Correlations were used to determine construct and concurrent validity of BPST with valid measures of spatial cognition and motor-cognitive integration. Performance was compared between PD and NT adults using independent t -tests. Results . BPST was feasible to administer. Analyses show evidence of construct validity for spatial cognition and for motor-cognitive integration. Concurrent validity was demonstrated with other tests of mobility and cognition. Relationships were stronger and more significant for individuals with PD than for NT individuals. BPST performance was not significantly different between groups. Conclusion . Tests that integrate cognitive challenge in mobility contexts are necessary to assess the health of spatial cognitive and motor-cognitive integration. The BPST is a feasible and valid test of whole-body spatial cognition and motor-cognitive integration in individuals with PD.